Fumonisin B1 induces oxidative stress in oesophageal (SNO) cancer cells. (January 2018) - Khan, René B.; Phulukdaree, Alisa; Chuturgoon, Anil A.
Abstract: Fumonisin B1 (FB1 ) is a ubiquitous contaminant of maize that is epidemiologically linked to oesophageal cancer (OC) in South Africa. FB1 -induced oxidative stress mediates toxicity in animals and human cell lines, but the effects relating to OC are limited. Given the species-specific effects of FB1, this study investigated FB1 -mediated toxicity and oxidative stress in spindle-shaped N-cadherin (+) CD45 (−) osteoblastic (SNO) cells. Following exposure to FB1 (0–20 μM) for 48 h, mitochondrial membrane potential and intracellular reactive oxygen species (iROS) were measured (flow cytometry). Malondialdehyde concentration (lipid peroxidation) was determined spectrophotometrically. ATP and reduced glutathione (GSH) concentrations were quantified using luminometry, gene expression of SOD2 by qPCR and protein expression of SOD2, GPx1, Nrf2 and HSP70 by western blotting. Mitochondrial depolarization increased at 10 μM and 20 μM FB1, with a concomitant reduction in ATP, iROS and GSH at both concentrations. Lipid peroxidation increased at 10 μM FB1 exposure. While transcript levels of SOD2 were significantly increased, protein levels decreased. Protein expression of GPx1, Nrf2 and HSP70 increased. In contrast to the 10 μM and 20 μM FB1 treatment, mitochondrial depolarization decreased at 1.25 μM FB1 . Intracellular ROS and ATP were decreased and lipid peroxidation increased. Decreased GSH was accompanied by a decrease in GPx1 protein levels, and increased HSP70 and Nrf2. SOD2 expression and protein levels were significantly increased. Overall these results indicate that FB1 caused increased ROS that were counteracted by engaging the antioxidant defense. Furthermore, the peculiar response at 1.25 μM FB1 is noteworthy, as compared to the other two concentrations tested. Highlights: FB1 induces oxidative stress in SNO (oesophageal) cells. FB1 altered mitochondrial membrane depolarization and depleted ATP. SNO cells induced a plethora of antioxidants to curb excess ROS levels. The lowest FB1 concentration (1.25 μM) displayed a peculiar response in the cells.